Responses to 7 October, law and society
1 online resource.
Keywords: "One of three volumes responding to the 7 October attack, Law and Society, begins with a legal, and a genocide studies critique of the claim that Israel is genocidal; another reflects on the absence of an understanding of antisemitism in international legal discourse. There are reflections on experiences in the Palestine solidarity movement and on the twists that discourse there takes. Contributions draw on Judaism, feminism and sociology to face what happened and to trace how Israelis were transported back to a quintessentially pre-Israel Jewish experience. Others survey reports of antisemitism around the globe in the wake of 7 October, including pieces about Britain and Germany. This work will appeal to scholars, students and activists with an interest in antisemitism, Jewish studies and the politics of Israel"--